PENGARUH TINGKAT KESEHATAN KEUANGAN PERBANKAN TERHADAP KREDIT YANG DISALURKAN - Yusian Tabita Aprilia; Rodhiyah Rodhiyah (Universitas Diponegoro, 2018)
One of the main function is to be mediator in credit distrubution. Bank credit distribution has credit risk indicated by NPL that tends to be higher. That is why elements which influence the bank credit distribution,well-condition of the bank itself, needs to be tested. This research objetive is to find the influence of risk profile (NPL), profit (ROA), and capital (CAR) to credit distribution ofBUSND . Research method using explanatory research with 56 samples through purposive sampling technique. Analysis techniques used are determination coefficient test, simple and double regression analysis, along with significance test of t and F. most of the LDR has been filled the regulation of BI but a small propotion less than optimal. Almost NPL is good though there are some higher than the regulation of Bank Indonesia. Most of the ROA are in a well condition All CAR have met the regulation of Bank Indonesia. NPL has no influence to LDR (0,862>0,05) and the coefficient of regressing is(0,153) while ROA influences LDR in (0,000<0,05) coefficient of regressing (-3,556). CAR influences LDR (0,020<0,05) and coefficient of regressing (0,595).Risk profile (NPL), profit (ROA) and capital (CAR) all together have impact to credit distribution (LDR) for (15,759 > 2,78, and 0,000<0,05. Bank must, strictly implement 5C to prefent high bad credit (NPL), increase the volume of credit distribution.